Impact of high-performance practices on financial and non-financial performance of organizations: the moderating role of employee productivity - Raja, Rehan; Iqbal, Muhammad Shahid; Hye, Qazi Muhammad Adnan; Adam Sa'ad, Auwal (Academia Publishing Group, 2024)
This study examines managerial and organizational factors associated with high-performance practices and high-performance Malaysian organizations. Theoretically, firm financial performance, organizational productivity, and market responsiveness are theorize d to be connected with a high-performanceorganization.Itisanticipatedthatemployees'productivitymoderatestherelationshipbetweennominatedexplanatoryanddependent variables, which are firm financial performance, organizational productivity, market responsiveness, and high -performance organizations. For investigating relationships among the variables, this study adopts the Partial Least Square Structural Equation Modeling (PLS-SEM) by using quantitative data from 186 firms' managers. The outcomes indicate that firm financial performance of an organization, organizational productivity, and market responsiveness are foundational building blocks for excellence in performance. The study found out that employee produ ctivity was the essential moderator in strengthening the relationship between organizational productivity, market responsiveness, and high -performance organizations, while firm financial performance had no significant moderating effect on high performance organizations. The findings are beneficial for the Malaysian firms’ managers to improve their financial and non-financial performance.